ره‌نگدانه‌وه‌ی بۆن له‌كاره‌ هونه‌رییه‌كانی(جه‌بار جه‌مال غه‌ریب و محمد اسماعیل)دا توێژینه‌وه‌یه‌كی ره‌خنه‌ی وه‌سفی شیكارییه‌ - MUSTAFA, REZAN OSMAN (Journal of Duhok University, 2023)
This research is a critical, descriptive and analytical research on (The Reflection of Smell in the Artworks by Jabbar Gamal Ghareeb and Muhammad Ismail) as an element of the aesthetic elements that motivates the artworks and their influence in moving the issue of narrative and vision in contemporary art, although few novelists and artists were interested in this subject, that’s why I decided to devote this research to deal with this element and explaining its characteristics in the novel (The People of the Sewers) and the works of the artist Mohamed Ismail, which he draws his works with coffee. This research consists of an introduction and three axes. In the introduction, we dealt with a definition and a brief overview of the history of smell. As for themes, we devoted the first axis to the dialectic of smell in philosophy and psychology, reviewing a group of contradictory opinions of philosophers, psychologists, philosophical schools and psychological schools about smell. In the second and third chapters, we talked about the philosophical and psychological dimensions in the novel (The People of the Sewers) and the paintings of the artist and their reflection in the structure of their dialogue on both sides.Relying on a set of literary examples and artwork for both artists within the framework of our research